ANALISIS BIAYA PENEBANGAN SISTEM SWAKELOLA: STUDI KASUS DI DUA IUPHHK-HA KALIMANTAN TENGAH - Soenarno (BRIN Publishing, 2017)
To improve the efficiency of timber harvesting process, forest industries have implemented tree length logging technique. Unfortunately, the effort in utilization as much as the tree parts has not been followed by minimizing the production cost, for example in the felling process. Industries apply a full contract felling system by involving third party even it is considered as an expensive cost. A solution of this problem is by implementing self-management felling system. This paper studies the felling cost conducted by third party and self-management. The study was carried out at two natural forest concessionaires (IUPHHK-HA) Central Kalimantan. Results reveal that self-managed felling system in both 3 3 IUPHHK-HA PT. A and PT. B costed about IDR 4,051.11/m and IDR 6,800.11/m , respectively. This cost is, 3 cheaper than the contract felling system which is ranged from IDR 6,000 to 7,000/m . Hence, for cost efficency, implementing self-management felling system is recommended.